The underlying factors of foreign language reading anxiety: Their effects on strategy use and orientation toward reading - Kim, Hyang Il (Studies in Second Language Learning and Teaching, 2021)
Both positive and negative emotions have been the focus of a wealth of language learning research in recent years. This can mostly be attributed to the established links between an individual’s psychological responses, existing and emerging from learning, the learning processes they engage in, and the outcomes they achieve. A look at advanced research on language anxiety, a negative emotion that appears to be strongly involved in learning, has shown that specific information about reading anxiety is comparatively insufficient. This study, therefore, examines the underlying factors of reading anxiety in Korean university students, using the Foreign Language Reading Anxiety Scale. Subsequently, it explores how these anxiety factors are related to strategy use (i.e., metacognitive, cognitive, and support strategies) and orientation toward reading, which demonstrates a reader’s active involvement while reading. Three sub-factors of reading anxiety were found: anxiety experienced during the process of reading English, confidence in reading, and anxiety when reading English characters. Interestingly, confidence or positive emotion was found to be a far more powerful positive contributor to Korean EFL university readers’ use of metacognitive strategies and the degree of orientation to reading than was anxiety experienced while reading. Pedagogical implications are discussed.